A retrospective cohort analysis of people living with HIV/AIDS enrolled in HIV care at a reference center in Antananarivo, Madagascar - Raberahona, Mihaja; Rakotomalala, Rado; Andriananja, Volatiana; Andriamamonjisoa, Johary; Rakotomijoro, Etienne; Andrianasolo, Radonirina Lazasoa; Rakotoarivelo, Rivonirina Andry; Randria, Mamy Jean de Dieu (Frontiers in Public Health, 2024)
Background The impact of the “Treat all” policy on the individual and in terms of public health is closely related to early diagnosis and retention in care. Patient-level data are scarce in Madagascar. In this study, we aimed to describe the profile of a cohort of newly diagnosed people living with HIV/AIDS (PLHIV), identify their outcomes, and assess factors associated with attrition from care and advanced HIV disease (AHD) at presentation. Methods We conducted a retrospective cohort study of PLHIV aged ≥15 years newly diagnosed at the University Hospital Joseph Raseta Befelatanana Antananarivo from 1 January 2010 to 31 December 2016. Results A total of 490 PLHIV were included in the cohort analysis. In total, 67.1% were male. The median age (interquartile range) at enrollment in care was 29 years (24-38). Overall, 36.1% of PLHIV were diagnosed with AHD at baseline. The proportion of patients with WHO stage IV at baseline increased significantly from 3.3% in 2010 to 31% in 2016 (p = 0.001 for trend). The probability of retention in care after the diagnosis at 12 months, 24 months, and 36 months was 71.8%, 65.5%, and 61.3%, respectively. Age ≥ 40 years (aHR: 1.55; 95% CI: 1.05–2.29; p = 0.026), low level of education (aHR:1.62; 95% CI: 1.11–2.36; p = 0,013), unspecified level of education (aHR:2.18; 95% CI: 1.37–3.47; p = 0.001) and unemployment (aHR:1.52; 95% CI: 1.07–2.16; p = 0.019) were independently associated with attrition from care. Factors associated with AHD at baseline were age ≥ 40 (aOR: 2.77; 95% CI: 1.38–5.57, p = 0.004), unspecified level of education (aOR: 3.80; 95% CI: 1.58–9.16, p = 0.003) and presence of clinical symptoms at baseline (aOR: 23.81; 95% CI: 10.7–52.98; p < 0.001). Sex workers were independently less likely to have an AHD at presentation (aOR: 0.23; 95% CI: 0.05–0.96, p = 0.044). Conclusion Sociodemographic determinants influenced retention in care more than clinical factors. The presence of clinical symptoms and sociodemographic determinants were the main factors associated with AHD at baseline.